PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN BAAMBOOZLE TERHADAP HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS DI SD NEGERI 167643 TEBING TINGGI - Angelina Rajagukguk, Nadia; Regina Sipayung; Antonius Remigius Abi; Bogor Lumbanraja; Nova Florentina Ambarwati; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of fourth grade students of State Elementary School 167643 Tebing Tinggi as seen from the results of daily test scores. This type of research is quantitative research using experimental methods and one group pretest-posttest design. The type of sample used is total sampling. The research sample used was 37 fourth grade students. Based on the results of the study, it shows that there is an influence of Problem Based Learning (PBL) Assisted by Baamboozle on the Learning Outcomes of Fourth Grade Students in the Science Subject at State Elementary School 167643 Tebing Tinggi in the 2024/2025 Academic Year, including the good category with an average of 78.59. The results of this study indicate that the results of the correlation test can be seen in the correlation coefficient value of 0.732, meaning that r_count (0.732)> r_table (0.324) means that Ha is accepted. So there is a strong influence between the Problem Based Learning Assisted by Baamboozle learning model on student learning outcomes. It can also be seen from the results of the t-test where t_count> t_table, namely 6.365> 1.687, thus stating that Ha is accepted. This shows a significant influence of the use of the Problem Based Learning learning model assisted by Baamboozle on the science learning outcomes of grade IV students at SD Negeri 167643 Tebing Tinggi in the 2024/2025 academic year.